2014
DOI: 10.1155/2014/489701
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nd Addition on the Microstructure and Martensitic Transformation of Ni-Ti Shape Memory Alloys

Abstract: The effect of rare earth element Nd addition on the microstructure and martensitic transformation behavior of Ni50Ti50−xNdx(x=0, 1, 3, 7, 20) shape memory alloy was investigated experimentally. The results showed that the microstructure of Ni-Ti-Nd ternary alloy consists of the NiNd phase and the NiTi matrix. One-step martensitic transformation was observed in all alloys. The martensitic transformation start temperatureMsincreased gradually with increasing Nd content for Ni-Ti-Nd alloys.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 13 publications
(17 reference statements)
0
3
0
Order By: Relevance
“…In this work, quaternary NiTiHfNd alloys with Nd content of 0, 1, 2 at.% were fabricated via arc melting, and the structure, phase transformation behavior, and the hardness were studied experimentally following our previously published studies [18][19][20]. It is found that Nd addition obviously decreases the martensitic transformation temperature of NiTiHf alloys but still maintains a relatively narrow thermal hysteresis and a relatively high Vickers hardness compared with most other components of NiTiHf-based alloys.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…In this work, quaternary NiTiHfNd alloys with Nd content of 0, 1, 2 at.% were fabricated via arc melting, and the structure, phase transformation behavior, and the hardness were studied experimentally following our previously published studies [18][19][20]. It is found that Nd addition obviously decreases the martensitic transformation temperature of NiTiHf alloys but still maintains a relatively narrow thermal hysteresis and a relatively high Vickers hardness compared with most other components of NiTiHf-based alloys.…”
Section: Introductionmentioning
confidence: 98%
“…Rare earth (RE) elements such as Ce [15], Gd [16], Dy [17], Nd [18], La [19] and Pr [20] have also been added to binary NiTi alloys to tune the phase transformation properties. The addition of Ce, Gd, and Dy to NiTi alloy increased the phase transformation temperatures because of some new-type second precipitates that exist in the NiTiRE alloys, which change the Ni/Ti ratio of the matrix [21].…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, but the addition of Hf and P d can increase the martensitic transformation temperature of N i − T i binary alloys. Moreover, the microstructure and martensitic transformation temperature of the addition of La [9] [10], Ce [11], P r [12], N d [13] [14], Gd [15], Dy [16] to N i − T i binary alloys have been studied using scanning electronic microscopy (SEM), energy dispersive spectrometry (EDS), X-ray diffraction (XRD), and differential scanning calorimetry (DSC). The addition of these rare earth elements to N i − T i binary alloys was found to increase the martensitic transformation temperature and change the phase transformation sequence.…”
Section: Introductionmentioning
confidence: 99%
“…NiTi alaşımlarında Ni elementi ile zengin olan NiTi bazlı şekil hatırlamalı alaşımlarda süper esneklik özelliği ön planda iken, Titanyum elementi bakımından zengin olan bu alaşımlarda önemli olan etken şekil hatırlama etkisidir [10,11]. NiTi bazlı şekil hatırlamalı alaşımlarda gerçekleşen faz dönüşümleri çoklu dönüşüm veya kademeli dönüşüm göstermektedir [12,13]. Genel olarak, R (rombohedral faz) fazı, B19 / fazından önce gözlemlenen kademeli dönüşümü temsil etmektedir.…”
unclassified